AN ANALYSIS OF AN ENGLISH TEXTBOOK ENTITLED “FORWARD AN ENGLISH” PUBLISHED BY ERLANGGA FOR TWELFTH GRADE VOCATIONAL SCHOOL STUDENTS - Diah Puspita Ayu; Susan Ira Nova; Lesly Martha Cecylia Meka; Sulamit Syeba (IKIP Siliwangi, 2024)
This research presents a thorough examination of the English course book titled